Outcome of the Public Consultation on the draft Guidance on Communication of Uncertainty in Scientific Assessments. Issue 1 (16th January 2019) - ,; Hart, Andrew; Maxim, Laura; Siegrist, Michael; da Cruz, Cristina; Merten, Caroline; Lahaniatis, Majlinda; Smith, Anthony
Abstract : The first strategic objective of EFSA's strategy 2020 'Trusted science for safe food' is the prioritisation of public and stakeholder engagement in the development of scientific assessment. To achieve this, objective public consultations are a key step for such a strategic framework. The draft Guidance document on communication of uncertainty underwent a web‐based public consultation from 4 May to 24 June 2018. The document provides guidance for communicators on how to communicate the various expressions of uncertainty described in EFSA's 'Guidance on uncertainty analysis in scientific assessments'. It also contains specific guidance for assessors on how best to report the various expressions of uncertainty. Overall, EFSA received 212 comments from 24 interested parties including academia, national agencies, nongovernmental organisations and communicators. This report lists the individual comments received and explains in detail how the comments were taken into account during the finalisation process of the 'Guidance on communication of uncertainty in scientific assessments'. EFSA wishes to thank all the commenters for their valuable contributions. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5520/full